\(x\sqrt{18}+\sqrt{18}=x\sqrt{8}+4\sqrt{2}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

12 tháng 9 2020

a) Ta có: \(\sqrt{4x-8}+5\sqrt{x-2}-\sqrt{9x-18}=20\)       \(\left(ĐK:x\ge2\right)\)

        \(\Leftrightarrow\sqrt{4}.\sqrt{x-2}+5\sqrt{x-2}-\sqrt{9}.\sqrt{x-2}=20\)

        \(\Leftrightarrow2.\sqrt{x-2}+5\sqrt{x-2}-3.\sqrt{x-2}=20\)

        \(\Leftrightarrow4.\sqrt{x-2}=20\)

        \(\Leftrightarrow\sqrt{x-2}=5\)

        \(\Leftrightarrow x-2=25\)

        \(\Leftrightarrow x=27\left(TM\right)\)

Vậy \(S=\left\{27\right\}\)

12 tháng 9 2020

a, PT <=> \(2\sqrt{x-2}+5\sqrt{x-2}-\sqrt{9\left(x-2\right)}=20\)

\(2\sqrt{x-2}+5\sqrt{x-2}-\sqrt{9}\sqrt{x-2}=20\)

\(\left(2+5-3\right)\sqrt{x-2}=20\)

\(4\sqrt{x-2}=20\Leftrightarrow\sqrt{x-2}=5\Leftrightarrow x-2=25\Leftrightarrow x=27\)

a: \(=2\sqrt{x-3}+3\sqrt{x-3}-4\sqrt{x-3}+3-x\)

\(=\sqrt{x-3}+3-x\)

c: \(\Leftrightarrow7\sqrt{x-2}-2\sqrt{x-2}-3\sqrt{x-2}=18\)

=>2 căn x-2=18

=>x-2=81

=>x=83

20 tháng 9 2017

a) \(\sqrt{25x+75}+3\sqrt{x-2}=2+4\sqrt{x+3}+\sqrt{9x-18}\) (ĐKXĐ : \(x\ge2\) )

\(\Leftrightarrow5\sqrt{x+3}+3\sqrt{x-2}-4\sqrt{x+3}-3\sqrt{x-2}=2\)

\(\Leftrightarrow\sqrt{x+3}=2\)

\(\Leftrightarrow x+3=4\)

\(\Leftrightarrow x=1\) ( Thỏa mãn ĐKXĐ )

20 tháng 9 2017

c) \(\sqrt{4x+20}+\sqrt{x+5}-\dfrac{1}{3}\sqrt{9x+45}=4\) (ĐKXĐ : \(x\ge-5\) )

\(\Leftrightarrow2\sqrt{x+5}+\sqrt{x+5}-\sqrt{x+5}=4\)

\(\Leftrightarrow2\sqrt{x+5}=4\)

\(\Leftrightarrow\sqrt{x+5}=2\)

\(\Leftrightarrow x+5=4\)

\(\Leftrightarrow x=-1\) ( Thỏa mãn ĐKXĐ )

Vậy.......

10 tháng 6 2015

\(x\sqrt{2}-x\sqrt{18}=\sqrt{27}-\sqrt{18}\Leftrightarrow x\sqrt{2}\left(1-3\right)=3\sqrt{3}-3\sqrt{2}\Leftrightarrow-2x\sqrt{2}=3\left(\sqrt{3}-\sqrt{2}\right)\)

\(\Leftrightarrow x=\frac{-3\left(\sqrt{3}-\sqrt{2}\right)}{2\sqrt{2}}\)

10 tháng 6 2015

\(x\sqrt{2}+3\sqrt{2}=x+3\sqrt{2}+3\sqrt{3}\Rightarrow x\left(\sqrt{2}-1\right)=3\sqrt{3}\Rightarrow x=\frac{3\sqrt{3}}{\sqrt{2}-1}\)

28 tháng 9 2019

2) \(\frac{1}{5}\sqrt{25x+50}-5\sqrt{x+2}+\sqrt{9x+18}+9=0\)

\(\frac{1}{5}\sqrt{25\left(x+2\right)}-5\sqrt{x+2}+\sqrt{9x+18}+9=0\)

\(\frac{1}{5}.\sqrt{25}.\sqrt{x+2}-5\sqrt{x+2}+\sqrt{9x+18}+9=0\)

\(\frac{1}{5}.5\sqrt{x+2}-5\sqrt{x+2}+\sqrt{9x+18}+9=0\)

\(\frac{1}{5}.5\sqrt{x+2}-5\sqrt{x+2}+\sqrt{9\left(x+2\right)}+9=0\)

\(\frac{1}{5}.5\sqrt{x+2}-5\sqrt{x+2}+\sqrt{9}.\sqrt{x+2}+9=0\)

\(\frac{1}{5}.5\sqrt{x+2}-5\sqrt{x+2}+3\sqrt{x+2}+9=0\)

\(\sqrt{x+2}-5\sqrt{x+2}+3\sqrt{x+2}+9=0\)

\(-\sqrt{x+2}=-9\)

\(x+2=81\)

\(\Rightarrow x=79\)

3) \(\sqrt{x^2-4x+4}=7x-1\)

\(\sqrt{x^2-2.x.2+2^2}=7x-1\)

\(\sqrt{\left(x-2\right)^2}=7x-1\)

\(x-2=7x-1\)

\(-2=7x-1-x\)

\(-2+1=7x-x\)

\(-1=6x\)

\(-\frac{1}{6}=x\)

\(\Rightarrow x=-\frac{1}{6}\)